Keterbacaan dan Kepraktisan Bahan Ajar Digital Gerak Melingkar Berbantuan Scratch Berbasis STEM untuk Mahasiswa - Zidatunnur, Silfia Fajriati; Rusilowati, Ani (UPEJ Unnes Physics Education Journal, 2021)
The purpose of this study to describe the characteristics, test the readability, and determine the practicality of teaching materials. This method used in this study is the Research and Development (R&D) method. The trial subjects were students of Physics education class 2018, Semarang State University. The characteristics of the teaching materials developed were the teaching materials displayed in the form of an e-book containing circular motion material integrated with aspects of STEM (Science, Technology, Engineering, and Mathematics) and equipped with a simulation using scratch. Based on the results of the readability test obtained an average readability score of 64.53% which indicates that the teaching materials developed have an easy to understand category. The result of the practicality test of teaching materials in term of ease of use, attractiveness of presentation, and benefits of teaching materials obtained an average of 84.88% practicality with the very practical category. These results indicate that the digital teaching materials in circular motion aided scratch based on STEM is easy to understand and very practical.